Pelatihan Pengelolaan Kelas Online Bagi Guru SMK Rijali Tulehu Kecamatan Salahutu Kabupaten Maluku Tengah - Mawar Indayani (IAIN AMBON, 2021)
Abstract: The problem of education personnel in ICT (Information and Communication Technology) for teaching and learning activities is still often encountered in Indonesia, including in Sukoharjo Regency. Science and Technology for the Community (IbM) which will be implemented at SMK Rijali is an effort to increase teacher professionalism in terms of the use of Information and Communication Technology (ICT) in learning. The output of IbM is in the form of a national journal with ISSN and a guide book. The general objective of implementing IbM is to increase teachers' understanding and skills regarding the use of ICT in online learning. The specific objectives of IbM include: (1) Teachers are able to use and manage online classes, (2) optimize existing information and communication technology facilities, and (3) increase the effectiveness, efficiency and attractiveness of learning. The methods that will be used in the implementation of IbM are socialization, practice, mentoring, and evaluation. This training material will be carried out in 2 stages where the first stage will focus more on providing information about materials related to the role of ICT in learning and the use of online classes. This information is very important so that the training participants get an idea of the role of ICT in learning, as well as the importance of training as a form of teacher self-development. The second stage of the training will focus on training on installation of online classes, management of learning materials, as well as making quizzes and online evaluation questions. With online classes, teachers are expected to be able to provide additional learning and evaluation anytime and anywhere. Evaluation of this activity is carried out during training activities and the results of making and managing online classes. Aspects that are evaluated are attendance, participant activity, participant understanding of the material that has been given. The criteria for achieving the program in each aspect are the attendance of participants, activities in good category, and level of understanding of the material in good category Keywords: Teacher Professionalism, Online Class Abstrak: Persoalan tenaga pendidikan dalam TIK (Teknologi Informasi dan Komunikasi) untuk kegiatan belajar mengajar masih sering di jumpai di indonesia termasukk di kabupaen Sukoharjo. Ipteks bagi Masyarakat (IbM) yang akan dilaksanakan di SMK Rijali merupakan satu bentuk upaya peningkatan profesionalisme guru dalam hal pemanfaatan Information and Communication Technology (ICT)dalam pembelajaran. Luaran IbM ini berupa jurnal nasional berISSN dan buku panduan. Tujuan umum pelaksanaan IbM adalah meningkatkan pemahaman dan keterampilan kepada guru tentang pemanfaatan ICT dalam pembelajaran online. Tujuan khusus dari IbM ini diantaranya: (1) Guru mampu menggunakan dan mengelola kelas Online, (2) mengoptimalkan fasilitas teknologi informasi dan komunikasi yang ada, serta (3) meningkatkan keefektifan, efisiensi dan daya tarik pembelajaran. Metode yang akan digunakan pada pelaksanaan IbM yaitu sosialisasi, praktek, pendampingan, dan evaluasi. Materi pelatihan ini akan di lakukan dalam 2 tahap dimana tahap pertama akan lebih fokus dalam memberikan informasi tentang materi berkaitan dengan peranan ICT dalam pembelajaran dan pemanfaatan kelas online. Informasi ini sangat penting dilakukan supaya para peserta pelatihan mendapatkan gambaran mengenai peran ICT dalam pembelajaran, serta pentingnya pelatihan sebagai bentuk pengembangan diri guru. Tahap kedua pelatihan akan fokus pada pelatihan instalasi pembuatan kelas online, pengelolaan materi pembelajaran, serta pembuatan kuis maupun soal evaluasi online. Dengan kelas online guru diharapkan bisa memberikan pembelajaran tambahan maupun evaluasi kapanpun dan dimanapun. Evaluasi kegiatan ini dilakukan saat berlangsungnya kegiatan pelatihan dan hasil pembuatan dan pengelolaan kelas online. Aspek yang dievaluasi adalah kehadiran, aktivitas peserta, pemahaman peserta terhadap materi yang telah diberikan. Kriteria pencapaian program setiap aspek adalah kehadiran peserta, aktivitas berkategori baik, dan tingkat pemahaman materi berkategori baik Kata kunci: Profesionalisme Guru, Kelas Online